2017
DOI: 10.1016/j.ymthe.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR-Cas9 to Generate Gene-Corrected Autologous iPSCs for the Treatment of Inherited Retinal Degeneration

Abstract: Patient-derived induced pluripotent stem cells (iPSCs) hold great promise for autologous cell replacement. However, for many inherited diseases, treatment will likely require genetic repair pre-transplantation. Genome editing technologies are useful for this application. The purpose of this study was to develop CRISPR-Cas9-mediated genome editing strategies to target and correct the three most common types of disease-causing variants in patient-derived iPSCs: (1) exonic, (2) deep intronic, and (3) dominant gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 73 publications
(98 reference statements)
1
96
0
Order By: Relevance
“…Human ipSc-tM exhibit morphology resembling ptM. Dermal fibroblasts or keratinocytes were obtained from three donors and induced pluripotent stem cells (iPSC) were generated using methods described earlier 13,14 . These iPSC were then differentiated into a cell type resembling TM cells (designated iPSC-TM) through co-culture with human primary trabecular meshwork cells (pTM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human ipSc-tM exhibit morphology resembling ptM. Dermal fibroblasts or keratinocytes were obtained from three donors and induced pluripotent stem cells (iPSC) were generated using methods described earlier 13,14 . These iPSC were then differentiated into a cell type resembling TM cells (designated iPSC-TM) through co-culture with human primary trabecular meshwork cells (pTM).…”
Section: Resultsmentioning
confidence: 99%
“…iPSC were derived from fibroblasts (lines A and C) or keratinocytes (line B) derived from 3 individuals without a history of glaucoma and reprogrammed using the CytoTune ® -iPS Sendai Reprogramming Kit (Invitrogen, MA, USA), as described earlier 13,14 . iPSCs were seeded in Corning Synthemax coated plates and cultured in TeSR-E8 media until they reached 5-10% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…While alleles can be effectively distinguished via CRISPR approaches in cases where a unique PAM is present in one allele [19,20], discrimination between alleles with single nucleotide mismatches within the sgRNA site is conceptually challenging given the promiscuity of sgRNA recognition [16,17,18]. In this regard, previous studies have shown promise in utilizing SNPs in the sgRNA target regions to achieve allele-specific mutagenesis [21,22,23,24,25]. Our results now extend allele-specific applications to HR-mediated gene targeting.…”
Section: Allele-specific Editing Of the Brca2 Locusmentioning
confidence: 76%
“…In cases of autologous transplantation, CRISPRi could be used to suppress the pathogenic gene in induced pluripotent stem cells (iPSCs) pre-implantation before reprogramming into the desired retinal cell type, and autologous transplantation. The potential of this treatment has been demonstrated with successful CRISPR/Cas9 gene correction of pathogenic retinal mutations in iPSCs for retinitis pigmentosa and Leber congenital amaurosis [59][60][61]. Following correction of three different RPGR frame shift mutations in patient iPSCs, Deng et al cultured the iPSCs into retinal organoids and found that the X-linked retinitis pigmentosa phenotype was completely alleviated [60].…”
Section: Ex Vivo Knock-downmentioning
confidence: 99%